2022
DOI: 10.1177/02841851221085674
|View full text |Cite
|
Sign up to set email alerts
|

High riding jugular bulb: prevalence and significance in asymptomatic children

Abstract: Background High riding jugular bulb (HJB) is a vascular abnormality characterized by the higher-than-normal location of the jugular bulb. Purpose To evaluate the frequency of HJB among children who underwent cranial computed tomography (CT) mostly because of head trauma. Material and Methods Patient demographics such as age, sex, indication of cranial CT, diameters of the right and left JB, and presence and laterality of HJB were recorded and analyzed. Patients were grouped as with HJB and without HJB; the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Aksoy et al found, in their series, that 53% of children with HRJB were younger than two years, while 86% of them were older than 12 months. The earliest case they found was eight-month-old [1]. Such observations suggest the HRJB may be congenital, or it develops early.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Aksoy et al found, in their series, that 53% of children with HRJB were younger than two years, while 86% of them were older than 12 months. The earliest case they found was eight-month-old [1]. Such observations suggest the HRJB may be congenital, or it develops early.…”
Section: Discussionmentioning
confidence: 95%
“…Okudera et al reported the JB does not appear before two years old [1,9,10]. They studied aborted fetuses and children up to six years and speculated that, during the fetal period and rst two years, bony and cartilaginous structures surrounding the JB prevent its development [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reportedly, the incidence of HJB ranges from 6% to 20% in patients undergoing computed tomography (CT) of the temporal bone for any reason (8,9). A recent retrospective study shows a prevailing rate of 42% for HJB (predominantly unilateral) among 194 children who underwent cranial CT primarily due to head trauma (10). Awareness of vascular abnormalities is beneficial in minimizing clinical complications during otologic surgery (11).…”
Section: Introductionmentioning
confidence: 99%